Penerapan Studi Green Marketing pada Pengukuran Niat Memilah Sampah Berdasarkan Perbedaan Generasi dalam Mengatasi Permasalahan Sampah di Bandung Raya - Yusuf, Teddy Rahardian; Sari, Hasrini (Program Studi Teknik Industri, Fakultas Teknologi Industri, Institut Teknologi Bandung, 2025)
The waste problem in Bandung City, including the ineffective waste segregation process, especially at the household level, is a significant problem. There needs to be public awareness, especially in sorting waste into organic, inorganic, and residual waste. Public awareness in managing waste requires beliefs, principles, and ethical considerations towards the environment based on the values of each individual. Nostalgia can be a medium or stimulus to foster the intention to engage in waste segregation activities or environmentally friendly practices. This research examines the influence of generational differences. Nostalgia has a different influence for each generation and becomes stronger with age. Each generation also has an influence on the values, place attachment, and attitude held by each individual. This study involved 236 respondents from the Greater Bandung area who were divided into three generational groups, namely Generation X-Baby Boomers, Generation Y, and Generation Z. The results showed that there were differences in nostalgia between generations. The results showed that there are differences in nostalgia, epistemic value, emotional value, place attachment, and attitude towards waste sorting behavior based on generation groups. This result is different for the intention to sort waste which has no difference for each generation. The government, especially the Bandung City Environmental Agency (DLHK), and profit and non-profit organizations can develop campaigns and programs that utilize nostalgia according to generation.